A design-based approach to support and nurture open educational practices. Issue 1 (2nd May 2017) - Karunanayaka, Shironica P.; Naidu, Som
Abstract : Purpose: A critical attribute of open educational practices (OEP) is the pursuit of open scholarship which comprises the release of educational resources under an open licence scheme that permits no-cost access, use, reuse, adaptation, retention and redistribution to others. The degree of openness in relation to this attribute will depend on the context and culture of the place and the people in it. When left to chance, the adoption and practice of open scholarship by educators is at best sketchy. For optimum impact, a design-based approach is essential. A central focus of such an approach will need to target educators' belief systems and practices about their scholarship. Any such work will involve researchers collaborating with practitioners in real-life settings to improve educational practices through iterative analysis, design, development and implementation. The purpose of this paper is to report on how the development and use of such a design-based approach, implemented by the Open University of Sri Lanka, impacted the adoption and uptake of open scholarship among teachers in the Sri Lankan school system in terms of changes in their use of instructional resources, pedagogical thinking and pedagogical practices. Design/methodology/approach: The study adopted a design-based research (DBR) approach (Reeves, 2006), which involved researchers collaboratively working with practitioners in real-life settings to improve their educational practices along three aspects – instructional resource use, pedagogical perspectives and pedagogical practices. Based on the four stages of the DBR approach – analysis, solution, testing and refinement, and reflection, a professional development intervention programme was designed and implemented to support teachers on the integration of open educational resources (OER) and adoption of OEP in their teaching-learning process. Data collected throughout the process using multiple strategies such as questionnaire surveys, concept mapping, lesson plans, focus group interviews, self-reflections and "stories", were analyzed using both qualitative and quantitative methods. Findings: By the end of the intervention, significant changes were observed in teachers' use of instructional resources, their pedagogical thinking and pedagogical practices. While resource usage has shifted from no or low usage of OER to reuse, revise, remix and creation of OER, the pedagogical thinking and practices of teachers moved from a content-centric and individualized patterns to more constructivist, context centric and collaborative ways. The diffusion of OEP was prominent along two dimensions – enhancements in the individual practices in innovative OER use as well as collaborative practices of sharing of resources, knowledge and good practices. Practical implications: The systematic and flexible methodology adopted based on the DBR approach via a framework designed as a contextualized, process oriented and a self-reflective enquiry has been very useful to support changes in OEP among practitioners over time. Originality/value: This iterative process allowed the researchers to function as "designers", while investigating real-life issues in collaboration with the practitioners through reflective enquiry to further refine innovative practices towards OEP. This provides valuable insights for improved design solutions for future interventions in similar contexts.